Recent progress in triboelectric platforms: engineering materials to industrial applications from the perspective of manufacturing - Yoonsang Ra; Minjun Song; Donghan Lee; Sunmin Jang; Yu-seop Kim; Joonmin Chae; Sumin Cho; Dongik Kam; Donghyun Lee; Gibeom Lee; Younghoon Lee; Dongwhi Choi (International Journal of Extreme Manufacturing)
With the growing importance of wearable and portable electronics in modern society and industry, researchers from all over the world have reported on advances in energy harvesting and self-powered sensing technologies. The current review discusses recent developments in triboelectric platforms from a manufacturing perspective, including material, design, application, and industrialization. Manufacturing is an essential component of both industry and technology. The use of a proper manufacturing process enables cutting-edge technology in a lab-scale stage to progress to commercialization and popularization with scalability, availability, commercial advantage, and consistent quality. Furthermore, much literature has emphasized that the most powerful advantage of the triboelectric platform is its wide range of available materials and simple working mechanism, both of which are important characteristics in manufacturing engineering. As a result, different manufacturing processes can be implemented as needed. Because the practical process can have a synergetic effect on the fundamental development, resulting in the growth of both, the development of the triboelectric platform from the standpoint of manufacturing engineering can be further advanced. However, research into the development of a productive manufacturing process is still in its early stages in the field of triboelectric platforms. This review looks at the various manufacturing technologies used in previous studies and discusses the potential benefits of the appropriate process for triboelectric platforms. Given its unique strength, which includes a diverse material selection and a simple working mechanism, the triboelectric platform can use a variety of manufacturing technologies and the process can be optimized as needed. Numerous research groups have clearly demonstrated the triboelectric platform’s advantages. As a result, using appropriate manufacturing processes can accelerate the technological advancement of triboelectric platforms in a variety of research and industrial fields by allowing them to move beyond the lab-scale fabrication stage.